Effect of different climatic environments on physiological characteristics of crossbred calves (Holandês X Gyr) (Revista de Ciências Agroveterinárias, 2016)
The aim of this work was to verify the adaptability of crossbred calves (Holstein x Gyr) created in the field and in the facilities in Bom Jesus, PI. Six crossbred calves (Holstein x Gyr) were distributed in two treatments: T1= Field and T2= Facilities, with three animals in each, with 32 repeated measurements over time, totaling 192 observations (6 animals x 32 repetitions per animal) during the experimental period. The physiological characteristics, such as respiratory rate (RR), heart rate (HR), rectal temperature (RT), and the sweating rate (SR) were recorded. The meteorological variables were: air temperature (AT), relative humidity (RH), globe temperature index and humidity (BGT1 and BGT2), where BGT1 was inside the facilities and BGT2 in the open field. All weather variables showed significant differences (p0.05). The RR was higher (p
Keywords: Adaptation; ambience; catle.